PENGARUH SENAM AEROBIK TERHADAP PENURUNAN GEJALA PRAMENSTRUAL SYNDROME PADA REMAJA PUTRI DI SMPN 1 BANGKALAN - Novi Anggraeni (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2018)
Pramenstrual Syndrome is a troublesomephysical, psychological and behavioral phenomenonthat is not caused by organic disease, whichregularly recurs during the cycle phase undergoingregression or disappearing during menstrual periods.The purpose of this study was to analyze the effectof decreased physical symptoms of pre menstrualsyndrome before and after aerobic exercise onadolescent girls SMPN 1 Bangkalan.The research design used is Pre Experimenttype One Group Pre-Test Post-Test Design. Thedependent variable in this study is the physicalsymptoms of pramenstrual syndrome, whereas theindependent variable is aerobic exercise. Thepopulation in this research is 45 people, with thesample number of 16 people in February 2017 in theworking area of SMPN 1 Bangkalan, the samplingmethod using Probability Sampling by SimpleRandom Sampling, taking data using questionnairesheet and using Wilcoxon Signed Rank TestThe results showed that before aerobicexercise was given (87.5%) teenage girlsexperienced pramenstrual syndrome physicalsymptoms with moderate category and after givenaerobic gymnastics most (81,25%) adolescent hadphysical symptoms of Pramenstral Syndrome withlight category. Wilcoxon Signed Rank Test Analysisshows that α = 0,05 and ρ = 0,01 thus ρ <α so thatH0 is rejected and Ha accepted that there isinfluence of aerobic gymnastics toward decreasingof physical symptoms of pre menstrual syndrome injuvenile girl SMPN 1 Bangkalan.The physical symptoms of PramenstrualSyndrome, can be corrected by improving lifestylechanges such as aerobic exercise to reduce thesymptoms that arise. Many other benefits of aerobicexercise for health such as increasing stamina andendurance